Um processo de formação continuada: das necessidades formativas às possibilidades de formação - Trevizan, Anaide (2008)
The social, politics e economics changes that it comes in the last few decades accruing in our society have affected the education, the schools and specifically the teacher s job. The professional knowledge acquired in the courses of initial formation shows off, usually, insufficient to answer to the challenges that the teacher finds in its teacher s practice daily. The creation of the continuing training spaces it s becomes fundamental to make possible to the teacher one analyze based of the challenges and faced problems on the classroom and the delineation of way for one effective teacher s practice. Searching better know the contributions of the continuing training for the teacher s performance, this research aimed to investigate the formative necessities of the teacher s at SESI-SP school net. The methodology of data collection was a type survey. A questionary witch closed and opened question was elaborated that was answered by 1.127 teachers, of which 656 of cycle I and 471 of cycle II, distributed by 21 formation regions in all the state of São Paulo. The theoretical referenciais that had endorsed the reflection had been sociohistorical psychology, represented by Vygotski thought, studies on the model of teacher s training and about formative necessities. A data gotten in the first part of questionary had allowed to make one characterization of the teacher s by referring to type or sort, age, academic formation e formation of graduate study. The great majority oh the teacher s are feminine sex, meets in age group between 30-40 years, on average has 12 years of teaching and made a specialization, beyond graduation. The data gotten in the second part of questionary had submitted analyze it of contents and congregate in three thematic blocks: continuing training in general; Formaprof the continuing training of the SESI-SP school net and formative necessities for one effective practice. About the aspects most general of the continuing training, the professor s had valued the training meeting for it s generate a reflection about practice and teacher s improvement. When they talk about the Formaprof, it s criticize the insufficient number of meeting per year, the extensive guide line and without focus and the continuity lock of the subjects. They praise the experience exchange and the explanation of doubt. The formative necessities more pointed by teachers are: the study of the learning expectations and the quarrel of the organized models for work axle; Knowledge about how to work with learning difficulties and the student inclusion